The relationship between vocal affect recognition and psychosocial functioning for people with moderate to severe traumatic brain injury: a systematic review. Issue 3 (14th December 2021) - Zupan, Barbra; Dunn, Leah; Hackney, Susanne; Shamshidinova, Bahtiyorhon
Abstract: The purpose of this review was to explore how vocal affect recognition deficits impact the psychosocial functioning of people with moderate to severe traumatic brain injury (TBI). A systematic review following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines was conducted, whereby six databases were searched, with additional hand searching of key journals also completed. The search identified 1847 records after duplicates were removed, and 1749 were excluded through title and abstract screening. After full text screening of 65 peer-reviewed articles published between January 1999 and August 2019, only five met inclusion criteria. The methodological quality of selected studies was assessed using the Mixed Methods Appraisal Tool (MMAT) Version 2018 with a fair level of agreement reached. A narrative synthesis of the results was completed, exploring vocal affect recognition and psychosocial functioning of people with moderate to severe TBI, including aspects of social cognition (i.e., empathy; Theory of Mind) and social behaviour. Results of the review were limited by a paucity of research in this area, a lack of high-level evidence, and wide variation in the outcome measures used. More rigorous study designs are required to establish more conclusive evidence regarding the degree and direction of the association between vocal affect recognition and aspects of psychosocial functioning. This review is registered with Prospero.